Treaties between the United States of America and the chiefs, headmen and warriors of the Potawattamie Indians : Mota, a Potawattamie chief and his band, Comoza, a Potawattamie chief and his band, and Muck Rose, a Potawattamie chief and his band : concluded December 4th, 10th, 16th and 17th, 1834, ratified March 16, 1835 ([publisher not identified], 1835)
The four treaties were concluded respectively, at Potawattamie Mills, Logansport, a camp on Lake Max-ee-nie-kue-kee and a camp on Tippecanoe River, in Indiana; all ratified by the Senate Feb. 26, 1835; signed by President Jackson Mar. 16, 1835.